1971
DOI: 10.1351/pac197127010023
|View full text |Cite
|
Sign up to set email alerts
|

Structure and thermodynamics of lanthanide and actinide complexes in solution

Abstract: Several questions of importance in the study of lanthanide and actinide coordination compounds are reviewed. There is considerable evidence that in aqueous solution the primary coordination number is nine for the ions La(m) through Nd(m) and eight for the ions heavier than Gd(m). While it seems that some degree of covalency exists in the metal-ligand bonding a model of electrostatic bonding seems satisfactory for explaining the structure and formation of the complexes. The dehydration of the lanthanide ions up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
62
0

Year Published

1973
1973
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(66 citation statements)
references
References 62 publications
4
62
0
Order By: Relevance
“…Lanthanide-isobutyrate complex stability is derived from a favorable entropy, the magnitude of which exceeds that of the unfavorable enthalpy contribution. Enthalpy-entropy compensation is a well-known but incompletely understood feature of lanthanide complexation reactions (50). Similar trends are seen for lactatepropionate, glycolate-acetate, and other structural analogs.…”
mentioning
confidence: 67%
“…Lanthanide-isobutyrate complex stability is derived from a favorable entropy, the magnitude of which exceeds that of the unfavorable enthalpy contribution. Enthalpy-entropy compensation is a well-known but incompletely understood feature of lanthanide complexation reactions (50). Similar trends are seen for lactatepropionate, glycolate-acetate, and other structural analogs.…”
mentioning
confidence: 67%
“…Thus, as the thermodynamic parameters AH° dS ° and dG ° discussed here were related to the whole extraction process, it should be noted here that those could not offer the information directly to the net complexation reaction. 13,14 Extractive separation of scandium(III) from lanthanoids(111) and yttrium (111) The solvent extraction experiments of rare earth elements(III) in HMBP-HN03 system showed that scandium(III) was quantitatively extracted as the acidity in the aqueous phase was greater than 1 mol dm 3 while all the lanthanoids(III) and yttrium(III) left in the aqueous phase (Fig. 4).…”
Section: Thermodynamicsmentioning
confidence: 99%
“…The aqueous solution of La(III) ions is dominated by their oxophilicity. 4,5 Lanthanide ions and their complexes are known to be excellent catalysts for the hydrolysis of biozide-type phenylphosphate esters of DNA and of related oligonucleotides 6,7 where the cleavage of nucleotides and of DNA or RNA by metal catalysts is an area of much current activity. 8 Good and coworkers 9 recommended a series of zwitterionic buffer compounds which are compatible with most media of physiological and biological importance.…”
Section: Introductionmentioning
confidence: 99%